2019
DOI: 10.1103/physrevc.100.024309
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the potential ultralow Q -value β -decay candidates Sr89 and Ba

Abstract: Background: Ultra-low Q-value β-decays are interesting processes to study with potential applications to nuclear β-decay theory and neutrino physics. While a number of potential ultra-low Q-value β-decay candidates exist, improved mass measurements are necessary to determine which of these are energetically allowed.Purpose: To perform precise atomic mass measurements of 89 Y and 139 La. Use these new measurements along with the precisely known atomic masses of 89 Sr and 139 Ba and nuclear energy level data for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Several potential ultra-low Q-value β -decay candidates have recently been studied via PTMS, for example 89 Sr, 131 Cs, 135 Cs and 139 Ba [28][29][30]. Among them, one promising candidate of the first-forbidden unique β − -decay transition, 135 Cs (7/2 + , ground state)→ 135 Ba (11/2 − , second excited state), was confirmed to be an ultra-low Q-value decay channel.…”
Section: Introductionmentioning
confidence: 99%
“…Several potential ultra-low Q-value β -decay candidates have recently been studied via PTMS, for example 89 Sr, 131 Cs, 135 Cs and 139 Ba [28][29][30]. Among them, one promising candidate of the first-forbidden unique β − -decay transition, 135 Cs (7/2 + , ground state)→ 135 Ba (11/2 − , second excited state), was confirmed to be an ultra-low Q-value decay channel.…”
Section: Introductionmentioning
confidence: 99%
“…where M p and M d are the mass of the parent and daughter atoms, respectively, and m e is the mass of the electron. The conversion factor from atomic mass units to keV, 1 u = 931 494.102 42 (28) keV/c 2 from Ref. [44] was used.…”
Section: Resultsmentioning
confidence: 99%
“…In collaboration with the LEBIT group at the National Superconducting Cyclotron Laboratory, we recently investigated and ruled out two candidates identified in Ref. [27]: 89 Sr and 139 Ba [28]. The JYFLTRAP group recently ruled out potential UL Q value decays in 72 As [29], and showed that 159 Dy does have an electron capture decay branch to an excited state in the daughter with a Q UL value of around 1 keV [30].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements at Penning trap facilities with ions from a LAS have spanned the nuclear chart from, for example, 6,7 Li [30] to 249 Cf [28]. Ions from a LAS serve as reference masses for on-line measurements with short-lived isotopes, calibrants for tuning a system and investigating systematics, and as the ions of interest for nuclear and neutrino physics studies, e.g., [31][32][33][34][35][36][37].…”
Section: Laser Ablation Source (Las)mentioning
confidence: 99%